Population-Based Trachoma Mapping in Six Evaluation Units of Papua New Guinea. (7th December 2016) - Ko, Robert; Macleod, Colin; Pahau, David; Sokana, Oliver; Keys, Drew; Burnett, Anthea; Willis, Rebecca; Wabulembo, Geoffrey; Garap, Jambi; Solomon, Anthony W.
ABSTRACT: Purpose : We sought to determine the prevalence of trachomatous inflammation – follicular (TF) in children aged 1–9 years, and trachomatous trichiasis (TT) in those aged ≥15 years, in suspected trachoma-endemic areas of Papua New Guinea (PNG). Methods : We carried out six population-based prevalence surveys using the protocol developed as part of the Global Trachoma Mapping Project. Results : A total of 19, 013 individuals were sampled for inclusion, with 15, 641 (82.3%) consenting to participate. Four evaluation units had prevalences of TF in children ≥10%, above which threshold the World Health Organization (WHO) recommends mass drug administration (MDA) of azithromycin for at least three years; Western Province (South Fly/Daru) 11.2% (95% confidence interval, CI, 6.9–17.0%), Southern Highlands (East) 12.2% (95% CI 9.6–15.0%), Southern Highlands (West) 11.7% (95% CI 8.5–15.3%), and West New Britain 11.4% (95% CI 8.7–13.9%). TF prevalence was 5.0–9.9% in Madang (9.4%, 95% CI 6.1–13.0%) and National Capital District (6.0%. 95% CI 3.2–9.1%) where consideration of a single round of MDA is warranted. Cases of TT were not found outside West New Britain, in which four cases were seen, generating an estimated population-level prevalence of TT in adults of 0.10% (95% CI 0.00–0.40%) for West New Britain, below the WHO elimination threshold of 0.2% of those aged ≥15 years. Conclusion : Trachoma is a public health issue in PNG. However, other than in West New Britain, there are few data to support the idea that trachoma is a cause of blindness in PNG. Further research is needed to understand the stimulus for the active trachoma phenotype in these populations.